Penerapan Model Pembelajaran Sentra Dalam Mengembangkan Kemampuan Sosialisasi Anak Usia Dini - Selvia Dewi; Safuri Musa; Ratna Sari Dewi (Peneliti.net, 2022)
The ability of children to socialize is an important thing that needs to be developed. In this stage of development, there will be many changes and create an ability. Sentra is one of the methods proposed by one of the educational leaders in the United States that stimulates children's intelligence through directed play so that it can create an active learning process in this case intelligence stimulates aspects of children's ability to socialize. The reason this topic was raised to find out the social skills that children have in one PAUD institution is really due to the application of the central learning model or there is a big role outside the center learning model. Based on the statement of Mukhtar Latif et al (2014:121) it was found that the concept of the center is that every activity that exists and is provided in all centers has a central point which all refers to the learning objectives. The concept of socialization is taken from Gunawan's (2012:198) statement which briefly states that socialization is an activity to convey messages to other people. The type of approach used in this research is qualitative with descriptive research methods. Through the research stage, collect data through observation, interviews and documentation, then analyze the data and conclude the data. There is great hope for further institutions and researchers that the results of this study can be used as a reference for school development and research